(untitled) (Indonesian Tax Justice Review, 2024)
Indonesia’s Omnibus Law on Taxation represents a major fiscal reform aimed at enhancing investment competitiveness and improving revenue performance. This paper examines the tax justice implications of the Omnibus Law, with particular attention to corporate income tax rate reductions, expanded tax incentives, and adjustments to value-added tax policy. Using doctrinal legal analysis and policy evaluation, the study assesses whether the reform advances distributive equity or exacerbates structural inequality. The findings indicate that while the Omnibus Law improves Indonesia’s attractiveness to capital, its benefits are unevenly distributed, favoring capital-intensive sectors and higher-income taxpayers. Reduced corporate tax rates and broadened incentives risk weakening vertical equity and constraining long-term revenue capacity. The paper argues that omnibus-style tax reforms in developing countries often prioritize efficiency and competitiveness over equity considerations. The global contribution of this study lies in providing a detailed case analysis of how comprehensive tax reforms in emerging economies interact with global tax competition pressures. Indonesia’s experience offers broader lessons for policymakers in developing countries considering similar legislative strategies, highlighting the need to embed tax justice principles explicitly within large-scale reform frameworks to ensure that competitiveness objectives do not undermine equitable fiscal outcomes.